Post-Attentive Integration and Topographic Map Distribution During Audiovisual Processing in Dyslexia : A P300 Event-Related Component Analysis - Siti Atiyah, Ali; Tahamina, Begum; Mohammed Faruque, Reza; Nor Asyikin, Fadzil; Faiz, Mustafar (Penerbit Universiti Sains Malaysia, 2020)
Background: Research on audiovisual post-attentive integration has been carried out using a variety of experimental paradigms and experimental groups but not yet studied in dyslexia. We investigated post-attentive integration and topographic voltage distribution in children with dyslexia by analysing the P300 event-related potential (ERP) component. Methods: We used a 128-child ERP net for the ERP experiment. Two types of stimuli were presented as either congruent or incongruent stimuli. Congruent stimuli included a matching auditory sound with an animal image, whereas incongruent stimuli included unmatched animal sounds. A total of 24 age-matched children were recruited in the control (n = 12) and dyslexia (n = 12) groups. Children pressed button ‘1’ or ‘2’ when presented with congruent or incongruent stimuli, respectively. The P300 amplitudes and latencies with topographic voltage distribution were analysed for both groups. Results: The dyslexia group evoked significantly higher P300 amplitudes at the T4 area than the control group. No significant differences were found in cases of P300 latency. Moreover, the dyslexia group demonstrated a higher intensity of P300 voltage distribution in the right parietal and left occipital areas than the control group. Conclusion: Post-attentive integration for children with dyslexia is higher and that this integration process implicated the parietal and occipital areas.